2009
DOI: 10.1111/j.1440-1746.2008.05573.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhubarb on migration of rat hepatic stellate cells

Abstract: The results suggest that rhubarb attenuated TGF-beta1-mediated migration of HSCs possibly by interfering with Smad2/3 phosphorylation, the MAPK pathway, and MMP-2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Second, ligation of HMGB1 to TLR4 can also activate other intracellular signal pathways besides JNK and PI3K/Akt signal pathway. For instance, MAPK / ERK signaling is involved in the HSCs proliferation and TGF-β1 can mediate the migration of HSCs possibly by Smad2/3 phosphorylation and MAPK pathway [47], [48]. Novo et al showed that mitochondrial-dependent ROS-mediated activation of ERK and JNK participated in hypoxia-induced migration of HSCs [49].…”
Section: Discussionmentioning
confidence: 99%
“…Second, ligation of HMGB1 to TLR4 can also activate other intracellular signal pathways besides JNK and PI3K/Akt signal pathway. For instance, MAPK / ERK signaling is involved in the HSCs proliferation and TGF-β1 can mediate the migration of HSCs possibly by Smad2/3 phosphorylation and MAPK pathway [47], [48]. Novo et al showed that mitochondrial-dependent ROS-mediated activation of ERK and JNK participated in hypoxia-induced migration of HSCs [49].…”
Section: Discussionmentioning
confidence: 99%
“…The result indicated that p-P38 and p-JNK were significantly elevated 30 min and 2 h after TGF-β treatment; this was consistent with the previous study. 41 However, we did not observe the elevation of p-ERK. We treated the HSCs with various concentrations of TGP (1−8 μg/mL) or propolin G (1−8 μM) prior to treatment with TGF-β for 15 min.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…The bottom wells were filled with serum-free medium co-treating with LPS plus Tan IIA (10 µM) or Sal B (200 µM) for 24 hr, and the entire chamber was incubated at 37°C for 24 hr. Cells migrated to the lower surface of the membrane were stained with hematoxylin (Sigma-Aldrich) to define the cell nuclei, as previously reported by us [32].…”
Section: Methodsmentioning
confidence: 99%